2010
DOI: 10.4238/vol9-4gmr953
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic findings in Serbian patients with Turner’s syndrome stigmata

Abstract: ABSTRACT. Cytogenetic findings are reported for 31 female patients with Turner's syndrome. Chromosome studies were made from lymphocyte cultures. Non-mosaicism 45,X was demonstrated in 15 of these patients, whereas only three were apparently mosaic. Eight patients showed nonmosaic and four patients showed mosaic structural aberrations of the X-chromosome. One non-mosaic case displayed a karyotype containing a small marker chromosome. Conventional cytogenetics was supplemented by fluorescence in situ hybridizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
3
9
1
Order By: Relevance
“…In our study, 43.6% of the TS cases were caused by 45,X monosomy, this being the most common cause of TS in our sample pool. These results were consistent with the data reported from other studies [Palmer and Reichman, 1976;Hall et al, 1982;Djordjevic et al, 2010]. X mosaicism including X/XX, X/XXX and X/XX/XXX was present in our sample pool at 11.2% whereas structural aberrations of the X chromosome were detected in 49 of 142 patients, corresponding to 34.5% of the population studied.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, 43.6% of the TS cases were caused by 45,X monosomy, this being the most common cause of TS in our sample pool. These results were consistent with the data reported from other studies [Palmer and Reichman, 1976;Hall et al, 1982;Djordjevic et al, 2010]. X mosaicism including X/XX, X/XXX and X/XX/XXX was present in our sample pool at 11.2% whereas structural aberrations of the X chromosome were detected in 49 of 142 patients, corresponding to 34.5% of the population studied.…”
Section: Discussionsupporting
confidence: 83%
“…Our cytogenetic analyses of 65 TS patients corroborated, in general, previously reported data (Held et al, 1992;Schoemaker et al, 2008;Djordjević et al, 2010;Elleuch et al, 2010). However, our patient sample had only one case (1.5%) of mosaicism with a normal cell line (46,XX), which is significantly lower than frequencies described in the literature (8 to 17%).…”
Section: Discussioncontrasting
confidence: 34%
“…Four other studies reported an association of X-monosomy with balanced Robertsonian translocation t(13;14) (Laszlo et al, 1984;Salamanca et al, 1985;Krajinovic et al, 1994;Silva et al, 2006). Recently, Djordjević et al (2010) showed a case of 45,X,t(1;9) (cen;cen) in combination with a r(X) mosaic karyotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, mosaic karyotypes were more frequent than isochromosomes, in contrast to what was expected. 29 It may be speculated that distribution of karyotypes did not alter the results in this study, since different karyotypes did not influence craniofacial morphology significantly.…”
Section: Discussionmentioning
confidence: 76%